Optimal Ordering Strategy of Perishable Products - Bjørvik, Simon Sagelv (UiT The Arctic University of Norway, 2016)
It is challenging to plan for the future, especially if there are uncertainties. In the retail store business making the right orders at the right time might have a severe impact on the profit of the store. Maintaining the right inventory is a part of this. With fluctuations in price and competition, having the best deals, and being at the whims of the customers making sure that the store has the correct amount of items in store is a challenge. By analyzing the historical sales data, we are able to make predictions for the expected sales. By doing this we can improve our inventory management to the point we are, at any time, able to meet the customer’s demands. The thesis has used statistical methods and tools to analyze the data, resulting in both a visual representation, and a simple mathematical representation of the analysis. In this thesis we used sales data for an item sold at Coop Obs Hypermarked Tromsø, and analyzed this to make predictions for the sales in the future. At the end of this thesis there have been made a suggestion for a simple inventory management of an item.